Analysis of land availability for utility-scale power plants and assessment of solar photovoltaic development in the state of Arizona, USA. (April 2019) - Majumdar, Debaleena; Pasqualetti, Martin J.
Abstract: Solar photovoltaic (PV) can help meet the growing demand for clean electricity in Arizona. This paper answers where solar PV development has taken place in Arizona, how much suitable land is available for utility-scale PV development, and how future land cover changes can affect the availability of this suitable land. PV development suitability scores are calculated for the land across Arizona based on topography, location, solar resource and public opinion factors. Ground truthing is used to identify the scenario which best explains Arizona's PV power plant developments from several decision-making scenarios. Less than two percent of Arizona's land is considered Excellent for PV development. Most of this land is private land or owned by state trust. If the available suitable land is fully developed with solar PV, Arizona has the potential to become a regional energy hub. However, in the next few decades suitable areas for solar PV generation can get rapidly depleted due to conflict with growing urban areas. If the suitable land for PV generation is not set-aside, Arizona would then have to depend on less suitable lands, look for multi-purpose land use options and distributed PV deployments to meet its future energy need. Highlights: Solar PV development is proposed to meet the growing demand for clean electricity in Arizona and in western USA. The study identifies suitable land for utility scale PV development in Arizona. GIS (Geographic Information System) and Multi-Criteria Analysis (MCA) are used. With the current available land for Solar PV, Arizona can meet its future energy demand and also be a regional energy hub. As urban Arizona grows with time, the land suitable for PV development would reduce significantly. I